2013
DOI: 10.1001/jamapediatrics.2013.1319
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Allergic Disease in Foreign-Born American Children

Abstract: Children born outside the United States have a lower prevalence allergic disease that increases after residing in the United States for 1 decade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
50
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 28 publications
(42 reference statements)
4
50
0
Order By: Relevance
“…A previous study found that children born outside the United States had dramatically lower odds of AD and allergic disease than those born in the United States [135]. One potential explanation is that less hygienic environmental exposures protect against developing AD and allergic disease.…”
Section: Hygiene Hypothesismentioning
confidence: 96%
See 1 more Smart Citation
“…A previous study found that children born outside the United States had dramatically lower odds of AD and allergic disease than those born in the United States [135]. One potential explanation is that less hygienic environmental exposures protect against developing AD and allergic disease.…”
Section: Hygiene Hypothesismentioning
confidence: 96%
“…One potential explanation is that less hygienic environmental exposures protect against developing AD and allergic disease. However, the odds of AD increased after residing in the United States for 10 or more years [135]. This suggests that the protective effects of early life exposures may eventually wear off.…”
Section: Hygiene Hypothesismentioning
confidence: 99%
“…4,5 The prevalence among recent immigrants is at the same scale as those reported for China and India, 3,16,17 major source countries of immigrants to Canada in recent decades. 18 Previous studies in other countries have also found a lower prevalence of allergies in immigrants compared with nonimmigrants, [19][20][21] and that longer duration of residence in the host country was associated with a higher prevalence of allergies among immigrants. 21,22 However, other studies have also reported null associations 23,24 or a higher prevalence of allergies among immigrants than non-immigrants.…”
Section: Discussionmentioning
confidence: 92%
“…18 Previous studies in other countries have also found a lower prevalence of allergies in immigrants compared with nonimmigrants, [19][20][21] and that longer duration of residence in the host country was associated with a higher prevalence of allergies among immigrants. 21,22 However, other studies have also reported null associations 23,24 or a higher prevalence of allergies among immigrants than non-immigrants. 25 Several factors may contribute to the inconsistency in research.…”
Section: Discussionmentioning
confidence: 92%
“…3 This suggests that 1 or more exposures in non-Westernized or developing countries may protect against chronic disease. Indeed, a previous study 4 found that foreign-born American children had dramatically lower prevalence of eczema and allergic disease than USborn American children. Furthermore, low prevalence of vitiligo (0.18%) has been reported in children in the Sinai Desert, suggesting a possible role for latitude in the development of the disease.…”
mentioning
confidence: 96%